Preliminary Phytochemical and Pharmacological Screenings of Plumbago indica L. and Alpinia conchigera Griff. - Ibrahim, Mohammed; Hossain, Md Aslam; Shajib, Md Shafiullah; Rashid, Mohammad A (Dhaka University Journal of Pharmaceutical Sciences, 2018)
The present study was conducted to evaluate the phytochemical constituents, anti-inflammatory, antipyretic, thrombolytic and CNS modulatory activities of the methanol, chloroform and n-hexane extracts of Plumbago indica L. and Alpinia conchigera Griff. The plants are used in the treatment of inflammations and fever in traditional systems of medicine in Bangladesh. Qualitative tests revealed that the crude extracts of the plants contain reducing sugars, steroids, alkaloids and flavonoids. The anti-inflammatory activity was evaluated by means of protein denaturation and membrane stabilization assay. The methanol extract of P. indica and A. conchigera demonstrated inhibition of protein denaturation by 34.55 and 29.55% while their n-hexane soluble extract exhibited 46.87 and 37.21% inhibition of lysis of erythrocyte membrane, respectively which were considerable as compared to the standard drug acetyl salicylic acid. The methanol extract of P. indica and A. conchigera prominently reduced Brewer’s yeast-induced pyrexia which were close to the standard drug, paracetamol. A considerable thrombolytic activity was exhibited by the chloroform soluble extract of A. conchigera (48.27%) compared to the reference drug, streptokinase (72.13%) in red blood cell clot lysis test. The chloroform soluble materials of P. indica extract demonstrated noticeable reduction of CNS depression activity (63.52 % inhibition of locomotion), compared to reference drug diazepam (80.69 %) in open field experiment. The study justifies the medicinal applications of P. indica and A. conchigera in traditional systems and reveals the bioactivity of the plants which could be suitable for isolation and identification of the bioactive compounds. Dhaka Univ. J. Pharm. Sci. 17(1): 73-79, 2018 (June)